2016
DOI: 10.1016/j.ebiom.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

ADAM30 Downregulates APP-Linked Defects Through Cathepsin D Activation in Alzheimer's Disease

Abstract: Although several ADAMs (A disintegrin-like and metalloproteases) have been shown to contribute to the amyloid precursor protein (APP) metabolism, the full spectrum of metalloproteases involved in this metabolism remains to be established. Transcriptomic analyses centred on metalloprotease genes unraveled a 50% decrease in ADAM30 expression that inversely correlates with amyloid load in Alzheimer's disease brains. Accordingly, in vitro down- or up-regulation of ADAM30 expression triggered an increase/decrease i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…It remains to be investigated whether this might contribute to the differences between C83 and C99 levels in TgMT5 −/− mice. In pace with the importance of proteolytic enzymes in APP trafficking and amyloidogenesis, another APP-interacting metalloproteinase, ADAM30, has been shown to promote APP sorting to lysosomes and degradation (Letronne et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…It remains to be investigated whether this might contribute to the differences between C83 and C99 levels in TgMT5 −/− mice. In pace with the importance of proteolytic enzymes in APP trafficking and amyloidogenesis, another APP-interacting metalloproteinase, ADAM30, has been shown to promote APP sorting to lysosomes and degradation (Letronne et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to further subsequent cleavage of already released Aβ peptides, Cathepsin B (Hook et al, 2005, 2014; Kindy et al, 2012), S and L (Schechter and Ziv, 2011) have been discussed to be directly involved in Aβ generation, acting as alternative β-secretases. The enzymatic cleavage events of cathepsins on APP are not fully understood since some groups showed that cathepsins are rather involved in Aβ degradation lowering total Aβ burden (Mueller-Steiner et al, 2006; Letronne et al, 2016). …”
Section: Conventional App Processingmentioning
confidence: 99%
“…Although we cannot exclude that other recently discovered APP-processing enzymes (e.g., meprin β, δ-secretase [1,39,2] might cooperate with MT5-MMP, this is rather unlikely because HEK cells do not constitutively express meprin β, and even when overexpressed, this metalloproteinase does not release sAPP95 [40,41]. Moreover, TIMPs do not inhibit meprins [42], while TIMP-2 efficiently blocked the generation of sAPP95 by MT5-MMP.…”
Section: The Generation Of Sapp95 By Mt5-mmp Does Not Involve Other Smentioning
confidence: 85%
“…Previous work reported the ability of the metalloproteinase ADAM30 to promote APP sorting in lysosomes by non-catalytic mechanisms. However, unlike MT5-MMP, the action of ADAM30 led to the degradation of APP by cathepsin D, thus preventing the formation of toxic APP catabolites[39]. Moonlighting actions of proteinases may logically require specific interactions of their non-catalytic domains with the target protein.…”
mentioning
confidence: 99%